Between Universalism and Particularism: the Reception of Noah, Abraham and Jacob Stories - Green, Stefan; Laato, Antti (Studies on the Children of Abraham, 2025)
The study deals with Jewish and Christian reception of the Book of Genesis and how the concepts "universalism" and "particularism" are used in Noah, Abraham and Jacob stories before the rise of Islam. As a synthesis of its discussed topics, the volume is a useful resource to understand early development of universalistic and particularistic ideas which became central theological topics in the three Abrahamic religions.